1999
DOI: 10.1002/cjce.5450770203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the gas/solids distributor on the local and overall solids distribution in a downer reactor

Abstract: In the last few years, the downer has been proposed as a new reactor for gadsolids reactions. Compared to state-ofthe-art riser reactoqthe cocurrent downflow of gas and solids should lead to a more uniform flow structure, close to plug flow. Experimental studies showed, that the gadsolids distributor at the top of the reactor is significantly influencing the flow pattern in a downer reactor. Local information about the solids concentration is indispensable for a thorough characterization of the flow structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The simulation was performed using a commercial CFD package of Ansys-uent V15.0 for modeling the CFB downer reactor. Numerous investigators [39][40][41] found that the ow behaviours in the downer reactor were symmetrical in theta coordinate. Thus, 2D simulation was generally applied for studying ow behavior and/or the performance of the reactive ow in downer reactors.…”
Section: Methodsmentioning
confidence: 99%
“…The simulation was performed using a commercial CFD package of Ansys-uent V15.0 for modeling the CFB downer reactor. Numerous investigators [39][40][41] found that the ow behaviours in the downer reactor were symmetrical in theta coordinate. Thus, 2D simulation was generally applied for studying ow behavior and/or the performance of the reactive ow in downer reactors.…”
Section: Methodsmentioning
confidence: 99%
“…The downflow of the downer plant is as well made of stainless steel with an inner diameter of 0.15 m and 8.5 m total height. 1st World Congress on Industrial Process Tomography, Buxton, Greater Manchester, April [14][15][16][17]1999 In order to measure the solids distribution inside both plants with the tomographic system four 0.5 m respectively 0.25 m long plexiglas tube elements are inserted between the stainless steel elements. With plexiglas tube elements instead of stainless steel elements the decrease in intensity only because of tube material is reduced.…”
Section: Methodsmentioning
confidence: 99%
“…group such as Bai et al, 1991a;Wang et al, 1992 and the Ž University Erlangen-Nurnberg research group Wirth et al, . 1998;Lehner et al, 1999 , which both show rather uniform radial profiles. One small difference is that they consistently observed a small peak near the wall, while we only observed the same in the middle developing portion of the downer.…”
Section: Radial Flow Structures In the Riser And The Downermentioning
confidence: 95%